Effects of exercise on heart function and tumor growth in mice with melanoma - Uurasmaa, Tytti (My University, 2019)
Millions of people are diagnosed with cancer every year. Many cancers are known to induce muscle wasting called cachexia. Cancer cachexia can lead to cardiac atrophy and disrupted cardiac function. Exercise has previously been shown to inhibit tumor growth and preserve heart function in tumor-bearing animals. However, it has not been investigated whether cancer increases cardiac hypoxia sensitivity and whether melanoma can disrupt cardiac function. Therefore, this study aimed to investigate whether melanoma disrupts heart function, especially in hypoxic conditions, and whether exercise can preserve heart function and inhibit tumor growth. The four test groups were exercising or untrained with or without melanoma. After average of 2.3-week running and monitoring tumor growth, the heart function was measured from isolated hearts using Langendorff method. Melanoma decreased mice running activity, but did not induce weight loss nor loss of heart mass during the study period. The heart function did not differ between the melanoma groups. Both melanoma groups had increased arrhythmia occurrence at a higher oxygen level than the untrained tumor-free animals, and lower generated afterload pressure amplitude and lower rate of pressure development. The tumor growth was slower in exercising animals only during the first two weeks of the experiment. In conclusion, melanoma decreased mouse running activity, disturbed heart function and increased cardiac sensitivity to hypoxia, but it did not cause weight loss or loss of cardiac muscle mass during the study period. Exercise in this study was sufficient to inhibit early tumor growth, but not for preserving heart function.
Keywords: cachexia, cancer, hypoxia, Langendorff method